Feeding Patterns, Mother-Child Dietary Diversity and Prevalence of Malnutrition Among Under-Five Children in Lebanon: A Cross-Sectional Study Based on Retrospective Recall - Abi Khalil, Huguette; Hawi, Mariam; Hoteit, Maha (Frontiers in Nutrition, 2022)
Background Despite demonstrated benefits, most countries fall short of meeting international targets for breastfeeding patterns, optimal complementary feeding, mother-children's quality diet, and malnutrition among under-five children. Rationale Since mothers usually play the most vital role in the healthcare of their children, research is needed to illuminate maternal factors that might promote a child's health and nutritional status. Aim The purpose of this study is to retrospectively (1) examine the under-five children's (0–59 months) feeding habits including exclusive breastfeeding, exclusive bottle feeding, continued breastfeeding, and complementary feedings, (2) investigate the mother-child's dietary diversity, and (3) identify any factors that cause less optimal nutrition due to a lack of food diversity in children aged 6 to 59 months. Moreover, (4) the prevalence of wasting, stunting, underweight, and overweight in the under-five offspring living in households located in the main two provinces in Lebanon (Beirut and Mount Lebanon) was determined. Methods The data for this analysis were collected from a representative sample of 384 households [384 mothers (21–49 years old) and children (0–59 months)] between February 2019 and June 2019. A questionnaire was used to inquire mothers of children ages 0–23 months about exclusive breastfeeding (EBF), continuous breastfeeding (CBF), exclusive bottle feeding (EBOT), mixed feeding (MF), and complementary feeding patterns. Moreover, additional questions regarding dietary diversity were asked to mothers of children aged 6 to 59 months. This score was calculated based on the 24 h recall of the mother and her child's consumption of 7 food groups, during the 24 h prior to the survey. Moreover, stunting, wasting, overweight, and underweight were calculated using the z-score for height-for-age (HAZ), weight-for-height (WHZ), and weight-for-age (WAZ), respectively. Binary logistic regression was used to explore the dietary diversity among children (ages 6–59 months) adjusting for covariates at maternal and household levels. Results Around 44% of children (0–59 months) had normal body weight. In addition, 9.3% were underweight (WAZ < -2SD to −3SD), 6.5% were at risk of being overweight, 24.45% were overweight, 9.3% were stunted (HAZ < -2SD to −3SD), and 6.25% (WHZ < -2SD to −3SD) were wasted. In total, among under-five children, the prevalence of EBF at 40 d and 6 months was 27 and 30%, respectively. The prevalence of CBF was 23%. Around 60% of mothers breastfed their offspring between 0 and 6 months and half of them introduced infant formula at earlier stages between 0–6 months. Furthermore, 78.4% of mothers introduced food to their children between 4 and 6 months (of which 40% before 6 months) and 62.5% of them introduced sugary drinks before 6 months. As for dietary diversity (DD), one out of two mothers and one out of three children (ages 6–59 months) had a low DD score (DDS) (46 and 32%, respectively). The children's and mother's DD were strongly found to be correlated (p-value = 0.034). Regression analysis showed that children's DD increased around 2 times [AOR = 1.7; 95% CI (1.042–2.914)] in context of high maternal DDS, and about 12 times [AOR = 11.7; 95% CI (1.2–111)] when a member of the highest-income households. Conclusions Our findings demonstrated low rates of EBF and CBF, high prevalence of EBOT, and early introduction of complementary foods among children ages 0–59 months. Furthermore, for children ages 6–59 months, there was poor mother-child dietary diversity and a high prevalence of overweight and stunted children in the main two Lebanese provinces. This suggests the alarming need for continuous nutrition intervention to improve infant feeding patterns and dietary diversity to reduce the malnutrition rates.